THE KINGDOM OF GOD AND THE ASSEMBLY OF THE PEOPLE: THE ROLE OF THE SYNAGOGUE IN THE AIMS OF JESUS - Ryan, Jordan J. (My University, 2016)
The four canonical Gospels describe the synagogues of the Land of Israel as the primary locus of the public activities of Jesus of Nazareth. Despite the prominence of synagogues in the extant accounts of Jesus’ life and career, academic research on early synagogues has not yet played a significant role in the study of the historical Jesus. This project incorporates the findings of recent research on ancient synagogues into the study of the historical Jesus. So doing helps to recover a piece of Jesus’ early Jewish context that has been frequently neglected or misunderstood in previous scholarship. This thesis has two related goals. The first is to contextualize Jesus’ activities in synagogues in light of current research on ancient synagogues. The second is to determine the role that the institution of the synagogue played in the aims of Jesus. I argue that the evidence indicates that the synagogue was intrinsic rather than incidental to Jesus’ mission, and that it was both the vehicle and the means by which he intended to realize his aim of the restoration of Israel. The historical investigation in this project helps to clarify our understanding of Jesus’ mission and also helps us to better understand the data involving synagogues in the Gospels. My examination of the evidence finds that the narratives involving synagogues in the Gospels accurately reflect an ancient synagogue setting, and can be better understood in light of current scholarship on synagogues. This speaks in favour of the historical plausibility of these narratives, and highlights the importance of the institutional setting of the synagogue for the interpretation of this data.
The Role of the Synagogue in the Aims of Jesus
Keywords: Jesus, Gospels, history, historiography, historical Jesus, synagogue, early synagogues, early Christianity, Gospel of Luke, religious studies, biblical studies, early Judaism